Latitudinal changes in submarine channel-levee system evolution, architecture and flow processes - Allen, Charlotte; Peakall, Jeff; Hodgson, David M.; Bradbury, Will; Booth, Adam D. (Frontiers in Earth Science, 2022)
Models of the sedimentary architecture of submarine channel-levee systems and their formative flow processes are predominantly based on studies from low latitude settings. Here, we integrate high-resolution seismic reflection, multi-beam bathymetry and GLORIA data to document the architecture and interpret the formative processes of a series of ultra-high latitude (72-76°N) submarine channel-levee systems that feed lobe complexes off the Greenland margin. We demonstrate that the sedimentary architecture of the channel-fills are dominated by vertical or near-vertical sediment accumulation, reflecting the lack of, or very limited nature of, lateral migration over time. All the Greenland channel-levee systems show significant cross-sectional asymmetry, and a peak sinuosity of 1.38, on a low gradient slope (~0.3). The bounding external levees are very thick (~200 m) and wide relative to low latitude systems. Comparison of these channel-levee systems with other examples reveals that these characteristics appear to be common to systems in high and ultra-high latitudes, suggesting latitudinal controls in the sedimentary architecture of submarine channel-levee systems. The differences between high- and low-latitude systems is likely due to the interplay of physical forcing (i.e. Coriolis force) and climatic factors that control sediment calibre and flow type, both of which are latitudinally dependent. Several formative mechanisms for supressing the initial phase of lateral migration and subsequent asymmetrical development are proposed, including: (i) rapid channel aggradation, (ii) Coriolis forcing causing preferred deposition on the right-hand side of the channel, and (iii) variance in flow properties, with traction- and suspension-dominated flows deposited on opposing sides of the channel. We argue that a high latitudinal location of larger channel-levee systems may result in the dominance of vertical stacking of channels, the construction of large external levees, and the development of a low sinuosity planform.